Fatal Lyme carditis and endodermal heterotopia of the atrioventricular node. Issue 772 (February 1990) - Cary, N. R.; Fox, B.; Wright, D. J.; Cutler, S. J.; Shapiro, L. M.; Grace, A. A.
Abstract : A fatal case of Lyme carditis occurring in a Suffolk farmworker is reported. Post-mortem examination of the heart showed pericarditis, focal myocarditis and prominent endocardial and interstitial fibrosis. The additional finding of endodermal heterotopia ('mesothelioma') of the atrioventricular node raises the possibility that this could also be related to Lyme infection and account for the relatively frequent occurrence of atrioventricular block in this condition. Lyme disease should always be considered in a case of atrioventricular block, particularly in a young patient from a rural area. The heart block tends to improve and therefore only temporary pacing may be required.